Equivalent Circuit Models for Impedimetric Sensors - Eva-Maria Korek; Evanthia Chrysanthi Kounoupioti; Ralf Brederlow (Proceedings)
In this work, equivalent circuit models for conductivity, reference, and potassium ion sensors are introduced and validated. The models help to understand and verify the sensors’ functioning and to determine the selective element of the potassium sensor as a capacitance that occurs below 1 Hz. Measurements at 100 mHz suggest that the phase response of the sensor reveals advantages concerning response time and stability compared to the typically used magnitude.